A Prospective Study on Assessment of Outcome of Patients with Rupture Uterus - Poorti Channana (Asian Journal of Medical Research, 2019)
Background: Uterine rupture is a major obstetric hazard. Gravid uterine rupture is associated with high maternal and perinatal mortality-morbidity rates and loss of future fertility. The present study was conducted to assess outcome of rupture uterus. Subjects and Methods: 84 cases of rupture uterus, with previous scarred or unscarred uterus during latent phase or active phase were included. Maternal and fetal outcome were recorded. Results: Age group <20 years had 10, 21-30 years had 30, 31-40 years had 36 and >40 years had 8 cases. Parity was o in 20, 1 in 24, >2 in 40, status was booked in 30 and unbooked in 54, type of rupture was scarred             in 20, unscarred in 10, complete in 19 and incomplete in 35. Perinatal outcome was normal fetus in 60, hypoxic injury in 17, perinatal mortality in 3 and malformed baby in 4. Maternal morbidity was anemia in 12, PPH in 4, ICU admission in 7 and maternal mortality in 3 cases. The difference was significant (P< 0.05). Conclusion: Most common type of rupture was incomplete followed by scarred.